Green technology innovation ecosystems in construction: strategies for value co-creation through evolutionary game theory - Dan Wang; Jinghan Liang; Onwe Joshua Chukwuma (Environmental Research Communications)
This study investigates the role of green technology innovation (GTI) in achieving sustainable development within the construction industry. It emphasises the importance of establishing an innovation ecosystem to enable value co-creation, moving beyond the traditional focus on construction enterprises as isolated entities. Using evolutionary game theory, an evolutionary game model is developed to explore value co-creation within the GTI ecosystem. The study examines the behavioural strategies of governments, construction enterprises, and consumers. Matlab software is employed for quantitative investigation, analysing the system’s stable strategy portfolio and evaluating the influence of key parameters on the evolution process and outcomes of value co-creation. The analysis reveals that E _8 (0,1,1) represents the ideal stable point in the system, with a defined evolution path to achieve this state. It highlights that excessive government intervention may hinder value co-creation, as overly high intervention intensity proves counterproductive. Construction enterprises are more sensitive to GTI costs than to the price of green building products, and substantial combined benefits of green building products are pivotal in shaping consumer decision-making. This study presents a novel GTI ecosystem model tailored for the construction industry and analyses the pathway for value co-creation. It provides strategic insights for fostering sustainable practices and contributes to the theoretical development of value co-creation within innovation ecosystems.